Parent’s Perspective about Intelligibility of Speech in Children with Cerebral Palsy - Muzna Khan, Aayeshah Firdous, Atia ur Rehman, Sadaf Hameed, Zunaira Zulqarnain, Ghulam Farid (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The term cerebral palsy (CP) refers to a collection of long-term abnormalities of posture and movement development that limit an individual’s activities. These abnormalities are thought to be caused by non-progressive disruptions in the growing fetal or infant brain. Aim: To identify the speech Intelligibility of children with cerebral palsy with different communicative partners Methods: This study employed convenient sampling over two months, conducted within the Pakistan Society for the Rehabilitation of the Disabled (PSRD) and Rising Sun Institute for Special Children. Data collection involved the ICS questionnaire, capturing parents’ ratings on their child’s speech intelligibility in various social contexts. Results: Out of 119 participants, predominantly aged 4 to 12 years, the study revealed varying levels of speech intelligibility. Scores on the Intelligibility in Context Scale (ICS). Parents exhibited a high level of understanding, with a mean score of 4.32±0.96 SD, signifying a substantial level of intelligibility. Immediate family members, extended family members, and the child’s teachers also demonstrated relatively high mean scores, ranging from 3.91 to 3.87. In contrast, strangers had a markedly lower mean score of 2.94±1.49 SD, indicating heightened challenges in comprehending the speech of children with cerebral palsy. Conclusion: The speech of children with cerebral palsy is most easily understood by parents, while strangers encounter more significant challenges. This reinforces the crucial role of familiarity in shaping speech intelligibility for these children. The observed difficulties in communication with unfamiliar individuals emphasize the need for targeted interventions and support to address the unique challenges faced by children with cerebral palsy in diverse social contexts. Keywords: Cerebral Palsy, Speech Intelligibility, Parental Perspective, Intelligibility in Context Scale (ICS)